2022
DOI: 10.14814/phy2.15369
|View full text |Cite
|
Sign up to set email alerts
|

Severe COVID‐19 correlates with lower mitochondrial cristae density in PBMCs and greater sitting time in humans

Abstract: An interaction between mitochondrial dynamics, physical activity levels, and COVID‐19 severity has been previously hypothesized. However, this has not been tested. We aimed to compare mitochondrial morphology and cristae density of PBMCs between subjects with non‐severe COVID‐19, subjects with severe COVID‐19, and healthy controls. Additionally, we compared the level of moderate‐vigorous physical activity (MVPA) and sitting time between groups. Blood samples were taken to obtain PBMCs. Mitochondrial dynamics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, it is not fully understood how mitochondrial cristae density or architecture is regulated. A potential regulator is inflammation, as we showed that COVID-19 patients with severe infection, characterized by higher systemic inflammation, had a lower mononuclear cell mitochondrial cristae density ( Castro-Sepulveda et al, 2022 ). Our study in human myotubes is the first to evaluate the effects of LPS on mitochondrial cristae architecture.…”
Section: Discussionmentioning
confidence: 94%
“…However, it is not fully understood how mitochondrial cristae density or architecture is regulated. A potential regulator is inflammation, as we showed that COVID-19 patients with severe infection, characterized by higher systemic inflammation, had a lower mononuclear cell mitochondrial cristae density ( Castro-Sepulveda et al, 2022 ). Our study in human myotubes is the first to evaluate the effects of LPS on mitochondrial cristae architecture.…”
Section: Discussionmentioning
confidence: 94%
“…PBMCs were separated under sterile conditions on Ficoll‐Histopaque 1077 (Sigma, Milan, Italy) gradients from ~10 mL of freshly drawn blood (see Castro‐Sepulveda et al., 2022 ) to obtain ~80% lymphocytes. PBMCs were frozen and stored at −80°C for Western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…We showed that PBMCs from COVID‐19 patients with acute inflammation present altered mitochondria morphology and mitochondria cristae architecture (Castro‐Sepulveda et al., 2022 ). Mitochondria are dynamic organelles that play an important role in highly active tissues, including skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%